A MODALITY ANALYSIS ON PRESIDENTIAL ELECTION AT 2019 IN INDONESIA: MULTICULTURAL STUDY - Sembiring, Sura Isnainy br; Nurlela, Nurlela; Mulyani, Rozanna (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2021)
A text modality system is a set of views, judgments, and opinions about linguistic phenomena. The theory used in this research is Systemic Functional Linguistics (SFL), which M.A.K Halliday initiated. This study's problem was to analyze the types and values of the modalities in the debate related to multicultural perspective. The data used in this study were 183 clauses and were analyzed qualitatively by using Functional Systemic Linguistic theory. Based on the results obtained through data analysis, Joko Widodo (Jokowi) nominated a probability modalization that shows the clause function as an exchange of information to express the speaker's attitude towards what he stated. Meanwhile, 80 types of modalities were found in Prabowo Subianto. They were nominated with the necessary modalities, which indicated that personal opinions or considerations were mandatory for the goods and services offered or requested.